18F-FDG PET Combined With MR Spectroscopy Elucidates the Progressive Metabolic Cerebral Alterations After Blast-Induced Mild Traumatic Brain Injury in Rats - Li, Yang; Liu, Kaijun; Li, Chang; Guo, Yu; Fang, Jingqin; Tong, Haipeng; Tang, Yi; Zhang, Junfeng; Sun, Jinju; Jiao, Fangyang; Zhang, Qianhui; Jin, Rongbing; et al. (Frontiers in Neuroscience, 2021)
A majority of blast-induced mild traumatic brain injury (mTBI) patients experience persistent neurological dysfunction with no findings on conventional structural MR imaging. It is urgent to develop advanced imaging modalities to detect and understand the pathophysiology of blast-induced mTBI. 18F-FDG PET could detect neuronal function and activity of the injured brain, while MR spectroscopy provides complementary information and assesses metabolic irregularities following injury. This study aims to investigate the effectiveness of combining 18F-FDG PET with MR spectroscopy to evaluate acute and subacute metabolic cerebral alterations caused by blast-induced mTBI. Twenty adult male Sprague Dawley rats were exposed to a single blast (mTBI group) and 20 rats were not exposed to the blast (sham group), followed by 18F-FDG-PET, MRI, and histological evaluation at baseline, 1-3 h, 1 day, and 7 days post-injury in three separate cohorts. 18F-FDG uptake showed a transient increase in the amygdala and somatosensory cortex, followed by gradual return to the baseline from day 1 to 7 days post-injury and a continuous rise in the motor cortex. In contrast, decreased 18F-FDG uptake was seen in the midbrain structures (inferior and superior colliculus). Analysis of MR spectroscopy showed inflammation marker myo-inositol (Ins), oxidative stress marker glutamine + glutamate (Glx), hypoxia marker lactate (Lac) levels markedly elevated over time in somatosensory cortex, while the major osmolyte taurine (Tau) level immediately increased at 1-3 h and 1 day, and then returned to sham level on 7 days post-injury, which could be reasoned by disruption of blood-brain barrier. Increased 18F-FDG uptake and elevated Ins and Glx levels over time were confirmed by histology analysis which showed increased microglial activation and gliosis in the frontal cortex. These results suggest that 18F-FDG PET and MR spectroscopy can be used together to reflect more comprehensive neuropathological alterations in vivo, which could improve our understanding of the complex alterations in the brain after blast-induced mTBI.